The Application of Sukuk Mudharabah and Sukuk Salam for Agricultural Sector Development in Indonesia - Nurfalah, Irfan (Fara'id and Wealth Management, 2023)
Agriculture sector has a strategic and important role for Indonesia's economic growth. The accured problems are lack of capital for developing this sector, agriculture modernism, uncommitted human resources and ignorance of farmer's welfare. At the same time, the development of sukuk develops rapidly in the world. Sukuk is used for financing all aspects that are needed into finance. So, this is such an opportunity for Indonesia to integrate sukuk for financing in developing agriculture sector in Indonesia. This paper proposes some concept of financing for developing agriculture sector with mudharabah sukuk and salam sukuk. This concept may achieve many capitals for agriculture in Indonesia. Because except the fund achieved for sukuk, the government also gives the budget allocation for this sector. Thus it, the capital problem such as technology, excellent seed, fertilizer, infrastructure, marketing and many other problems may overcome soon